Epidemiological profile of Aids cases reported in Brazil from 2009 to 2019 (Research, Society and Development, 2020)
Infection with the Human Immunodeficiency Virus (HIV) affects T lymphocytes, leading to progressive depletion and causing progressive and continuous immune impairment, which can lead to Acquired Immunodeficiency Syndrome (Aids). Given that HIV infection and Aids are public health problems worldwide, it is important to know their epidemiological profile in Brazil. Thus, this research is a retrospective ecological study, descriptive with a quantitative approach to the number of Aids cases notified in Brazil from 2009 to 2019. The data show that a total of 283.188 cases were reported. The majority affect individuals of the male gender, in the age group of 30 to 39 years old, of white color/race and with education level referring to complete high school. There is a predominance of heterosexual individuals and most cases were reported in the Southeast region. It is noted that although the spread of HIV infection at a national level has shown changes in its epidemiological profile, there is still a profile characterized by a process of heterosexualization, feminization and interiorization according to what has been established in the last decades in Brazil.